2014
DOI: 10.1152/ajpheart.00844.2013
|View full text |Cite
|
Sign up to set email alerts
|

The presence of the NOS3 gene polymorphism for intron 4 mitigates the beneficial effects of exercise training on ambulatory blood pressure monitoring in adults

Abstract: The number of studies that have evaluated exercise training (ET) and nitric oxide synthase (NOS)3 gene polymorphisms is scarce. The present study was designed to evaluate the relationship between exercise training and NOS3 polymorphisms at -786T>C, 894G>T, and intron 4b/a on blood pressure (BP) using 24-h ambulatory BP monitoring (ABPM), nitrate/nitrite levels (NOx), and redox state. Eighty-six volunteers (51 ± 0.6 yr old) were genotyped into nonpolymorphic and polymorphic groups for each of the three position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 70 publications
2
18
0
4
Order By: Relevance
“…Most of studies examining the lactacidemic responses were performed in athletes or healthy subjects with low physical fitness whereas studies investigating hypertensive subjects, mainly women, are scarce. In this sense, it is important to evaluate such parameters in hypertensive women using walk on treadmill, which is particularly interesting for this population when considering characteristics of the disease, especially with respect to the benefits on cardiovascular system promoted by moderate-intensity aerobic exercise widely proven in this type of ergometer when prescribed at appropriate intensities 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of studies examining the lactacidemic responses were performed in athletes or healthy subjects with low physical fitness whereas studies investigating hypertensive subjects, mainly women, are scarce. In this sense, it is important to evaluate such parameters in hypertensive women using walk on treadmill, which is particularly interesting for this population when considering characteristics of the disease, especially with respect to the benefits on cardiovascular system promoted by moderate-intensity aerobic exercise widely proven in this type of ergometer when prescribed at appropriate intensities 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Office BP and Ambulatory BP monitoring (ABPM) were obtained in accordance with international guidelines as described previously (Sponton et al, 2014).…”
Section: Anthropometric and Cardiovascular Parametersmentioning
confidence: 99%
“…Is there an endothelial dysfunction after menopause? Previous studies have systematically shown that NO/cGMP signaling pathway, as well as flow-mediated dilation, is not impaired in hypertensive postmenopausal women as compared with normotensive subjects (Sponton et al, 2014;Puga et al, 2016;Jarrete et al, 2016;Novais et al, 2017). Additionally, both hypertensive and normotensive postmenopausal women were responsive to aerobic exercise training (AET) by increasing the endothelial biomarkers related to NO/cGMP pathway (Sponton et al, 2010;Rezende et al, 2011).…”
mentioning
confidence: 99%
“…We recently found that the classification of obesity based on DXA measures along with biochemical and inflammatory parameters appears to be a more accurate method and to have a major clinical importance as compared with BMI, as it allows the differentiation of the lipid profile between eutrophic and overweight older women (Funghetto et al, 2015). Recently (Sponton et al, 2014), it was found that the presence eNOS gene polymorphism for the positions T786-C and G894T390 did not affect the beneficial effect of aerobic exercise training on blood pressure, neither cardiometabolic biomarkers in sedentary non-obese middle-aged subjects. Comparisons between studies are very difficult because the polymorphism position, exercise protocol and subjects evaluated are different, which limits more precise conclusions.…”
Section: Dependent Variablementioning
confidence: 99%